Investigation on curdlan dissociation by heating in water. (September 2017) - Xiao, Man; Jiang, Mingfeng; Wu, Kao; Yang, Hao; Ni, Xuewen; Yan, Wenli; Phillips, Glyn O.; Jiang, Fatang
Abstract: This study aimed to investigate molecular aggregation of curdlan on heating in water through atomic force microscopy (AFM), transmission electron microscopy (TEM), turbidity, and rheology tests. With improved sample preparation methods, AFM and TEM analysis revealed that curdlan morphologies changed with heating temperatures. Bundles of curdlan triple-stranded helixes had mainly hydration and swollen process at 40 °C, and bundled triple-stranded helixes were driven to separate from each other at 50 °C. These triple-stranded helixes would dissociate into partially opened triple-helical chains and single-helical chains at 60and 70 °C, and finally large amounts of dissociated single-helical chain were presented at 80 and 90 °C. Accordingly, structures of curdlan at temperatures ranging from 25 to 90 °C were proposed, and the turbidity and rheology results could be well explained with proposed structures. This research may provide new insights on revealing the behaviour of curdlan water dispersions on heating in water alone. Graphical abstract: Highlights: Methods of curdlan samples preparation for AFM and TEM observation were improved. Curdlan triple-helical chains began to dissociate into single-helical chains at 60 °C. Large amounts of single-helical chain were presented at 80 and 90 °C. Rheology result was consistent with the proposed curdlan structures.